Determination of the modes of action of a cationic surfactant for property development in carbon black filled natural rubber compounds - Ismail H; Din R H; Freakley P K; Ishiaku U S (Polymer International, 1996)
Work to separate the contributions of fatty diamine surfactant (termed a multifunctional additive [MFA]) to property development, from mastication, elastomer-filler interface and crosslink density effects has been carried out. Improvement in mechanical peoperties resulting from the MFA is dominated by its effect on carbon black dispersion, compared with its effect on crosslink density. Results show that there is a slight improvement in resistance to crack initiation (tensile test) and a substantial improvement in resistance to crack growth (tear strength) as MFA level increases compared with the results for control compounds (extended mixing time compounds). This improvement is attributed to the influence of the MFA on energy dissipation at the rubber-carbon black interface.
Source Year: 1996
Keywords: Carbon black; Cationic surfactant; Natural rubber